Study of use of antiseptic ice of plasma-chemically activated aqueous solutions for the storage of food raw materials - Pivovarov, Oleksandr; Півоваров, Олександр Андрійович; Kovalova, Olena; Ковальова, Олена Сергіївна; Koshulko, Vitalii; Кошулько, Віталій Сергійович; Aleksandrova, Angelina; Александрова, Агеліна (Одеський національний технологічний університет, 2021)
Scientists and specialists of food processing industry are increasingly focused on the technology of storage of raw materials of animal origin in antiseptic ice. The paper presents the peculiar features of plasma-chemical activation of solutions to produce antiseptic ice and their further use in the storage of meat and fish. The process of treatment leads to formation of micro-particles of hydrogen peroxide, which in contact with the raw materials are capable of generating active oxygen, allowing to disinfect the raw material surface. Concentration of hydrogen peroxide in the solutions further used to produce antiseptic ice has been determined. Study of the features of use of antiseptic ice made of plasma-chemically activated aqueous solutions showed unchanged organoleptic properties of raw materials after using the presented antiseptic agent. Suppression of viable microflora owing to antimicrobial action of plasma-chemically activated aqueous solutions was recorded. Antiseptic ice contributes to long-term disinfection of raw materials. For example, the samples show absence of microflora of mesophilic aerobic and facultative anaerobic microorganisms and bacteria of the Escherichia coli group, which allows improving the quality of stored food raw materials. At the concentration of peroxides at the level of 600-700 mg/l, pathogenic microflora in meat and fish samples is not present at all. When meat and fish raw materials are stored in ice for 30 days, pathogenic microflora does not appear, and it confirms the long-term disinfecting action of antiseptic ice. Slower accumulation of amino-ammonia nitrogen is observed during long-term storage of meat and fish raw materials. The use of plasma-chemically activated aqueous solutions for the production of antiseptic ice and storage of meat and fish raw materials in it can partially prevent the processes of protein breakdown and, accordingly, increase the product shelf life. The paper describes technological parameters of the process of storage of meat and fish in antiseptic ice, which can be used in the industrial storage of raw materials, and provides the guidance for use of ice of plasma-chemically activated aqueous solutions in the process of storage of raw materials of animal origin. Технологія зберігання сировини тваринного походження в антисептичному льоді стала об’єктом підвищеної уваги вчених та фахівців харчопереробної промисловості. У роботі наведено особливості плазмохімічної активації розчинів для виробництва антисептичного льоду та їх подальше використання при зберіганні м’яса і риби. У процесі такої обробки утворюються мікрочастки пероксиду водню, які при контакті з сировиною здатні утворити активний кисень, що дозволяє дезінфікувати поверхню сировини. Визначено концентрацію пероксиду водню в розчинах, які в подальшому використовувались для отримання антисептичного льоду. Дослідження особливостей використання антисептичного льоду з плазмохімічно активованих водних розчинів показало, що при використанні представленого антисептика органолептика сировини була незмінна. Відмічено пригнічення життєздатної мікрофлори, за рахунок антимікробної дії плазмохімічно активованих водних розчинів. Антисептичний лід сприяє тривалому знезараженню сировини. Так в зразках відмічається відсутність мікрофлори мезофільних аеробних і факультативно-анаеробних мікроорганізмів та бактерій групи кишкової палички, що дозволяє покращити якість харчової сировини, що зберігається. При концентрації пероксидів на рівні 600-700 мг/л відмічається повна відсутність патогенної мікрофлори у зразках м’яса і риби. При зберіганні в льоді м'ясної та рибної сировини протягом 30 діб патогенна мікрофлора не з’являється, що підтверджує тривалу дезінфікуючу дію антисептичного льоду. Під час тривалого зберігання м’ясної та рибної сировини відмічене більш повільне накопичення аміно-аміачного азоту. Використання плазмохімічно активованих водних розчинів для виробництва антисептичного льоду і зберігання в ньому м’ясної і рибної сировини дозволяє частково попередити процеси розкладання білків і, відповідно, збільшити строки зберігання продукту. У роботі висвітлено технологічні параметри процесу зберігання м’яса та риби в антисептичному льоді, які можуть бути використані при промисловому зберіганні сировини. Наведено технологічні рекомендації щодо використання льоду з плазмохімічно активованих водних розчинів в процесі зберігання сировини тваринного походження.
Дослідження використання антисептичного льоду з плазмохімічно активованих водних розчинів при зберіганні харчової сировини
Keywords: plasma-chemical activation; плазмохімічна активація; aqueous solutions; водні розчини; hydrogen peroxide; перекис водню; antiseptic ice; антисептичний лід; meat; м'ясо; fish; риба